KARAKTERISTIK MUTU BAWANG GORENG PALU SEBELUM PENYIMPANAN - Andi Ete; Nur Alam Nur Alam (Universitas Tadulako, 2009)
The research aimed to determine the quality characteristics (physical, chemical, microbiological and organoleptic) of pre-storage Palu fried onions before storage and to identify factors affecting the quality characteristics. To achieve the purpose of the study a series of activities was conducted including selection/determination of samplse, identification and analysis of physical, chemical, microbiological and organoleptic components of 10 selected samples of fried onions. The results showed the lowest value for water content (1.88%) was in the sample I, oil (30.64%) in the sample H, ALB (0.17%) in the samples B, C and G, minerals (2.51% ) in the sample F, KBC (7.99%) in the sample C, and total microbes (10 colonies / g) in the samples E and J. The most crispy texture (F max 0.12 N) was in the sample I. The highest value for the aroma score (3.33) was in the sample E, taste (3.97) in the sample D, crunchiness (4.07) and preference (3.80) in the sample B. The highest quality characteristics of fried onions before the storage was found in the sample B and I, followed by samples D, E, G, C, J, A, H, and F, respectively. The factors affecting the quality characteristics of Palu fried onion before storage included (1) the level of mixed materials used was still very high, (2) continous reusing of oil, (3) uncontrollable frying temperature, (4) short time for reducing oil content, and (5) thin and not airtight packaging materials.